'All the corridors are the same': a qualitative study of the orientation experiences and design preferences of UK older adults living in a communal retirement development. Issue 9 (28th March 2017) - O'MALLEY, MARY; INNES, ANTHEA; MUIR, SARAH; WIENER, JAN M.
ABSTRACT: Environments need to be designed such that they support successful orientation for older adults and those with dementia who often experience marked difficulties in their orientation abilities. To better understand how environments can compensate for decreasing orientation skills, voice should be given directly to those experiencing dementia to describe how they find their way and to understand their design preferences. This study explored the navigational experiences and design preferences of older adults with memory difficulties living in a retirement development. In-depth semi-structured interviews with 13 older adults experiencing memory difficulties were conducted. All participants were residents of one retirement development in the United Kingdom. Questions began broadly, for example, to describe their experiences of navigating in their living environment, before discussing any specific navigation difficulties in detail. Thematic analysis identified three main themes: highlighting environmental design that causes disorientation, strategies to overcome disorientation, and residents' suggestions to improve the design. The design suggestions were particularly informative, heavily focusing on the importance of having memorable and meaningful spaces which were favoured more than signage as an orientation aid. The findings demonstrate the need to consider environmental design to support orientation for those with memory difficulties. Of particular importance is the use of meaningful and relevant landmarks as orientation aids which can additionally stimulate conversation and increase wellbeing. Given the range of suggestions in dementia-friendly design guidelines aimed to support orientation, it is crucial to speak directly to those living in different environments to learn how they find their way around and what design works in their environment.